Structural and metamorphic inheritance controls strain partitioning during orogenic shortening (Kalak Nappe Complex, Norwegian Caledonides). (July 2020) - Ceccato, A.; Menegon, L.; Warren, C.J.; Halton, A.M.
Abstract: The occurrence of pre-collisional structural and metamorphic fabrics may control the development of new structures during subsequent orogenic deformation. Structural, petrological and geochronological analyses have been performed on selected samples collected along a NW-SE cross section of the Kalak Nappe Complex (KNC) exposed on Kvaløya Island (Finnmark, Norway), in order to define pre-Caledonian or Caledonian affinity of deformation fabrics. Nappes within the KNC experienced different pre-collisional tectonometamorphic histories, resulting in contrasting pre-Caledonian fabrics, which in turn controlled orogen-scale strain partitioning and metamorphic re-equilibration during Caledonian shortening. Caledonian deformation during top-to-SE-directed thrusting occurred at 550–675 °C and 0.8–1.0 GPa in the presence of fluids. Suitably-oriented pre-collisional fabrics were firstly exploited as zones of localized shearing internal to the KNC and subjected to metamorphic re-equilibration during shortening. Fold geometry during Caledonian thrusting was also controlled by the orientation of pre-Caledonian fabrics. SE-verging asymmetric folds were developed after minor tilting of pre-Caledonian upright folds with orogen-parallel hinge in the hinterland consistently with top-to-SE shearing. Shear-parallel folds displaying orogen-perpendicular hinge lines resulted from top-to-SE general shearing of pre-collisional upright folds showing pre-collisional orogen-perpendicular hinge lines. Caledonian metamorphism appears to have been accompanied by infiltration of radiogenic 40 Ar-rich fluids, which affected the Ar isotopic system in synkinematic micas. Highlights: Poly-orogenic units of the Kalak Nappe display different orogenic shortening styles. Poly-orogenic units of the Kalak Nappe experienced different pre-Caledonian P-T paths. Inherited fabric orientation and metamorphic assemblage(s) control strain partitioning. Metamorphic fluid infiltration contaminated the Ar system in synkinematic micas.